The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.2147/dddt.s237301
|View full text |Cite
|
Sign up to set email alerts
|

<p>Effects of Apatinib on the Pharmacokinetics of Nifedipine and Warfarin in Patients with Advanced Solid Tumors</p>

Abstract: Background and Purpose: Apatinib is a small-molecule tyrosine kinase inhibitor for the treatment of recurrent or progressive advanced-stage gastric adenocarcinoma or gastroesophageal junction cancer. The in vitro inhibition studies suggested that apatinib exerted potent inhibition on CYP3A4 and CYP2C9. To evaluate the potential of apatinib as a perpetrator in CYP450-based drug-drug interactions in vivo, nifedipine and warfarin were, respectively, selected in the present study as the probe substrates of CYP3A4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…Zhu et al have investigated the potential of apatinib as a perpetrator on the pharmacokinetics of nifedipine and warfarin in advanced solid tumor patients. The results indicated that concomitant administration of apatinib led to an obvious increase to nifedipine and warfarin exposure ( Zhu et al, 2020 ). Due to the risk of pharmacokinetic DDI based on enzyme inhibition by apatinib, a dynamic PBPK model is needed for further dosing recommendations when apatinib is co-administered with CYP3A4, CYP2D6, or CYP2C9 substrates.…”
Section: Discussionmentioning
confidence: 99%
“…Zhu et al have investigated the potential of apatinib as a perpetrator on the pharmacokinetics of nifedipine and warfarin in advanced solid tumor patients. The results indicated that concomitant administration of apatinib led to an obvious increase to nifedipine and warfarin exposure ( Zhu et al, 2020 ). Due to the risk of pharmacokinetic DDI based on enzyme inhibition by apatinib, a dynamic PBPK model is needed for further dosing recommendations when apatinib is co-administered with CYP3A4, CYP2D6, or CYP2C9 substrates.…”
Section: Discussionmentioning
confidence: 99%
“…The in vitro studies indicated that nifedipine was a typical substrate of CYP3A4 which was almost completely metabolized by CYP3A4 (Guengerich et al, 1986). The research conducted by Zhu et al (2020) has confirmed that co-administration of nifedipine with apatinib significantly increased the AUC 0-48h and C max of nifedipine by 83% and 64%, respectively. Coadministration of apatinib with nifedipine could cause exposure changes of nifedipine in vivo.…”
Section: Introductionmentioning
confidence: 89%
“…Summary of the input data are listed in Table 2. Apatinib was reported to exert potent inhibition on CYP3A4 in a competitive way (Zhu et al, 2020). In the DDI models between nifedipine and apatinib, the K i was set to 0.12, with the f umic at 0.65 (Bao et al, 2018;Zhu et al, 2020).…”
Section: Development Of Nifedipine-apatinib Drugdrug Interaction Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Apatinib, as a selective vascular endothelial growth factor receptortyrosine kinase inhibitor, has an inhibitory effect on various solid tumours, such as advanced hepatocellular carcinoma and GC. [3][4][5] Long non-coding RNAs (lncRNAs) are a kind of non-coding RNA with a length of more than 200 nucleotides. LncRNAs regulate the expression of genes from multiple levels such as chromatin remodelling, transcription and post-transcription.…”
Section: Introductionmentioning
confidence: 99%